Variation of the Hydraulic Conductivity of Clayey Soils in Exposure to Organic Permeants - Hanane Mortezaei; Mehran Karimpour Fard (Civil Engineering Journal, 2017)
Clayey soils are the most common material used in waterproofing and play an essential role in waste and contamination control. Permeability is a key parameter in such problems and its determination is needed in ensuring the satisfactory performance of the soil. Research has shown that a permeant fluid with a low dielectric constant can shrink the double layer around the clay particles which will, in turn, increase the permeability of the soil. In this paper, the permeability of two types of clay with different plasticity, exposed to the flow of water and methanol as polar and miscible solvents and gasoline and car oil as non-polar and immiscible solvents is investigated. In addition, the effect of soil properties such as plasticity and compaction water content on permeability of the samples is examined. To this end, soil samples are prepared and compacted at various water contents. Then, permeability tests are conducted according to the modified constant head method and the effects of parameters such as the fluid dielectric constant, water content of the samples and soil plasticity are examined. The results demonstrate that the lower dielectric constant of the organic fluid decreases the thickness of the double layer, providing more space for the flow of the permeant and as a result, the permeability of the clay increases. The reduction of the permeant dielectric constant from 80.4 to 2.28 led to a remarkable increase in soil permeability.